Deletion of Opg Leads to Increased Neovascularization and Expression of Inflammatory Cytokines in the Lumbar Intervertebral Disc of Mice. Issue 1 (1st January 2017) - Li, Xiao-Feng; Xue, Chun-Chun; Zhao, Yong-Jian; Cheng, Shao-Dan; Zhao, Dong-Feng; Liang, Qian-Qian; Chen, Lin; Wang, Qiang; Lu, Sheng; Shi, Qi; Wang, Yong-Jun; Shu, Bing
Abstract : Study Design: Neovascularization and expression of inflammatory cytokines were examined in Osteoprotegerin ( Opg) knockout (KO) mice that show intervertebral disc (IVD) degeneration. Objective: The aim of this study was to clarify the pathological changes in lumbar IVD degeneration in Opg KO mice. Summary of Background Data: Osteoporosis is a controversial risk factor for IVD degeneration. Deletion of Opg resulted in IVD degeneration in mice. Neovascularization and inflammatory cytokines are key factors in IVD degeneration. Methods: Opg KO mice and their wild-type (WT) littermates were euthanized. Lumbar IVDs were harvested. Safranin O/Fast Green staining was performed to examine the pathological changes. Microcomputed tomographic (micro-CT) analysis was performed to determine the structural changes at the junction of lumbar IVD cartilage and vertebrae. Tartrate-resistant acid phosphatase (TRAP) staining was performed to evaluate osteoclast formation. Protein expression of vascular endothelial growth factor A (VEGF-A), CD31, VE-cadherin, CD 34, interleukin-1β (IL-1β), and tumor necrosis factors α (TNF-α) were analyzed by immunohistochemistry (IHC) assays. Gene expressions of IL-1β, IL-6, and TNF-α were analyzed by real-time polymerase chain reaction (RT-PCR). Results: In 12-week-old Opg KO mice, new bone was formed in the endplate cartilage of lumbar IVDs and this became more obvious in 24-week-old Opg KO mice. Three-dimensional (3D) μCT reconstruction analyses showed that the edges of the L4 and L5 vertebrae were rugged with bone marrow cavities in it. Protein expression of VEGF-A, CD31, VE-cadherin, and CD34 was increased in the endplate and growth plate of lumbar IVDs of Opg KO mice. Gene expression of IL-1β, IL-6, and TNF-α as well as protein expression of IL-1β and TNF-α were highly expressed in the lumbar IVDs of Opg KO mice. Conclusion: Deletion of Opg leads to increased neovascularization and expression of inflammatory cytokines in the lumbar disc in Opg KO mice, which may play important roles in IVD degeneration. Level of Evidence: N/A